Ferroelectric and Non-Linear Optical Nanofibers by Electrospinning: From Inorganics to Molecular Crystals - Rosa M. F. Baptista; Etelvina de Matos Gomes; Michael Belsley; Bernardo Almeida (Nanomaterials)
In recent decades, substantial progress has been made in embedding molecules, nanocrystals, and nanograins into nanofibers, resulting in a new class of hybrid functional materials with exceptional physical properties. Among these materials, functional nanofibers exhibiting ferroelectric, piezoelectric, pyroelectric, multiferroic, and nonlinear optical characteristics have attracted considerable attention and undergone substantial improvements. This review critically examines these developments, focusing on strategies for incorporating diverse compounds into nanofibers and their impact on enhancing their physical properties, particularly ferroelectric behavior and nonlinear optical conversion. These developments have transformative potential across electronics, photonics, biomaterials, and energy harvesting. By synthesizing recent advancements in the design and application of nanofiber-embedded materials, this review seeks to highlight their potential impact on scientific research, technological innovation, and the development of next-generation devices.